Study On The Effects Of Alternative-Kerosene Fuel Mixture On Combustion Spray Characteristics For Different Spray Half Cone Angle - Roslan, Farah Syafiqah (Universiti Sains Malaysia, 2018)
This study focuses on simulating a two-dimensional (2D) case of a simple cylindrical combustion chamber to study the effects of alternative-kerosene fuel mixture on combustion spray characteristics for different spray half cone angles. The simulation is performed by using Computational Fluid Dynamic (CFD). The fuels that are used for the simulation are Jet-A, Jatropha Bio-synthetic Paraffinic Kerosene (JSPK), and Camelina Bio-synthetic Paraffinic Kerosene (CSPK). Additionally, the mixture of 50% JSPK with 50% Jet-A (50JSPK/50Jet-A) and the mixture of 50% CSPK with 50% Jet-A (50CSPK/50Jet-A) are used to examine the effects of blend fuel. Every fuel is simulated at 30°, 40° and 50° of injection spray half cone angle. The velocity of the fuel injection spray is considered in X and Y direction. The results obtained is compared in terms of the temperature profile, spray penetration and injection discrete particle model evaporation. From the simulation, it is found that as the spray half cone angle increases, the distance of the maximum temperature increases, the final temperature increase, the time taken for droplet to evaporate increases and discrete phase model evaporation decreases. At 40° and 50° spray half cone angle, Jet-A has the shortest time taken to completely evaporate and highest DPM evaporation which is then followed by 50JSPK/50Jet-A, 50CSPK/50Jet-A, JSPK and CSPK. Furthermore, Jet-A has the shortest distance to completely evaporate and it is followed by JSPK, 50CSPK/50Jet-A, 50JSPK/50Jet-A and CSPK.